Modifikasi Algoritma Caesar Cipher pada Kode ASCII dalam Meningkatkan Keamanan Pesan Teks - Mira; Hindriyanto Dwi Purnomo; Irwan Sembiring (Institut Shanti Bhuana, 2022)
Abstract— Theft of personal data is a criminal act and violates the law in the field of information technology. Therefore, the security of personal data must have a higher level of security. Personal data security can be done by one of them providing a password to the data file. To avoid password burglary, you can encrypt the password. This study uses the Caesar Cipher algorithm in the encryption process. However, some classical cryptographic algorithms that have been widely known have weaknesses that can be solved by cryptanalysis. Therefore, to avoid this, before encrypting, the caesar cipher algorithm is modified first and then converted into ASCII code. The results of the modified algorithm provide a level of message security complexity, when compared to the caesar algorithm without modification. This is shown from the results of the ciphertext that produces ciphertext in the form of combined characters, making the ciphertext more difficult to read and understand by humans, so as to increase message security and can minimize the occurrence of hacking by irresponsible parties.